THE INFLUENCE OF MULTIMEDIA-BASED MOBILE LEARNING MEDIA ON ENGLISH LEARNING OF CLASS VII STUDENTS - Epi Supriyani Siregar; Ika Purnama Sari; Ikhwan Mahfud Hidayat; Imanuddin; Puji Hariati, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study aims to investigate the effect of using multimedia-based mobile learning media on the English learning outcomes of class VII students. This research was conducted in a junior high school where class VII students were the research subjects. The experimental method is used to measure student learning outcomes before and after carrying out learning using mobile learning media. The research results show that the use of multimedia-based mobile learning media significantly improves student learning outcomes in English. The average student score on the initial test before media use was 65, while on the final test after media use it increased to 88. These results indicate that mobile learning media can be facilitate students' understanding of English material better. Apart from that, mobile learning media also provides visual and interactive support that allow students to understand the material more deeply. The flexibility and accessibility of this medium also allows students to learn at the time and place of their choosing. This is relevant to students' learning preferences in the current digital era. This research has positive implications for the development of English learning methods. Educators can consider using multimedia-based mobile learning media as an effective learning tool to improve students' understanding and learning achievement in English subjects. Further studies can delve deeper into the use of this media in the context of sustainable education. Thus, the results of this research provide an important contribution for understanding the influence of mobile learning media on English language learning and providing guidance for educators to utilize it effectively in the learning process.